On the Application of the LIC=(KIC/OYS)2 Criterion to Fracture of Cracked Pipes - Mihovsky, I.M. (Engineering Transactions, 1980)
The results of certaio experiments on propagation of cracks in internally pressurized pipes are analysed as a known criterion based upon using the quantity LIC as a parameter governing the conditions for crack growth initiation. Formally, LIC is equal to the squared ratio of the material plane strain fracture toughness to its yield stress in pure tension. It is shown that such a criterion is in good agreement with the experiments on crack growth initiation in pipes fabricated from typical ductile structural steels. The criterion is applicable to both through-wall and part-through-wall (surface) cracks.